An example of career counselling with college students at a Brazilian private university - Lorentz, Cacilda Nacur; Cirino, Sérgio Dias (ICAReAlumni Conference Proceedings, 2020)
The complexity and dynamism of the 21st-century labor market entails challenges for higher education in all countries of the world. Young people seek qualifications to help them start a career and enter the job market. To this end, they seek to pursue a higher education that can positively impact their social mobility and career building prospects. However, nowadays, having a college degree alone neither ensures a successful career, nor guarantees employability. The present report exposes the experiences of implementing a career counseling project for students from a private college in the city of Belo Horizonte, Brazil. This project will be referred to here as the "Careers Project." The aim of the project was to support and accompany college students by giving professional guidance, helping them plan their careers, and contributing to the development of skills that are valued in the context of the current job market. It was intended to facilitate exchanges between the academic and organizational environments, thereby making the job market more accessible to students.